BATIK FRAKTAL: PERKEMBANGAN APLIKASI GEOMETRI FRAKTAL - Romadiastri, Yulia (Delta Jurnal Ilmiah Pendidikan Matematika FKIP Universitas Pekalongan, 2013)
Fractal geometryis a branch ofmathematicsthat studies offractalshapes. Fractalsareshapes thatlookirregularbut are actuallymorecloselyifthere isa patternobservedregularityin it. Fractalshaveinfinitedetailandcanhave astructureof self-similarity atdifferentmagnificationlevels. Inmanyforms, it can be obtainedby repeating thefractalpatternto infinitytimes. The development offractalgeometryitself has beenfound ina variety offields, one of whichisthemaking ofbatikpatternwhich istypical ofIndonesianculture. unique andbeautifulbatikpatterns can be obtainedFrom this fractalforms. This of coursecanalsoenrich theculture of Indonesia. Â Kata Kunci: geometri, fraktal, batik